2016
DOI: 10.3171/2015.7.spine15353
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation rates for symptomatic nonunions in posterior cervical (subaxial) fusions with and without bone morphogenetic protein in a cohort of 1158 patients

Abstract: OBJECTIVE Bone morphogenetic protein (BMP) was first approved in 2002 for use in single-level anterior lumbar fusions as an alternative to iliac crest grafts. Subsequent studies have concluded that BMP provides superior fusions rates and therefore reduces reoperations for nonunions. The purpose of this study was to determine the reoperation rates for symptomatic nonunions in posterior cervical (subaxial) spinal fusions with and without the use of BMP and to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…14,15,18,19,25 The majority of these studies report a higher radiographic fusion rate with BMP, but there may not be a substantial difference in clinically significant nonunion—defined as pseudarthrosis requiring revision—between these groups. 18,19,25 This question of clinical significance is important and is particularly relevant to the subject of BMP. The Yale Open Data Access (YODA) Project, for example, found that the use of BMP likely leads to an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15,18,19,25 The majority of these studies report a higher radiographic fusion rate with BMP, but there may not be a substantial difference in clinically significant nonunion—defined as pseudarthrosis requiring revision—between these groups. 18,19,25 This question of clinical significance is important and is particularly relevant to the subject of BMP. The Yale Open Data Access (YODA) Project, for example, found that the use of BMP likely leads to an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…The use of BMP in the posterior cervical spine, however, has been recently examined in several retrospective studies without the airway complications reported with anterior use. 14 18 These studies have shown rates of nonunion ranging from 0% to 10.3% with the majority showing an improvement fusion rates based on computed tomography imaging. Other authors, focusing on posterior BMP use at the cervicothoracic junction, found that the use of BMP did not result in a significantly different rate of symptomatic non-union requiring reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…Again, we believe operative nonunion rates are useful and clinically relevant and can be used to compare BMP to non-BMP patients as we have shown in other studies. [20][21][22] We also acknowledge there are some limitations to our study. It is a retrospective study, which may have inherent selection biases.…”
Section: Discussionmentioning
confidence: 99%
“…In previous articles we have introduced the use of reoperation rates for nonunions as a possible outcome measure, combining both radiographic studies and clinical symptoms. [20][21][22] We believe this is an important outcome measure for both patients and health care payers and is worthy of adding to the literature. Hence, the objective of our study is to report the reoperation rates for symptomatic nonunions in a large cohort of patients with posterior cervicothoracic spine fusions from a spine registry and to compare these rates with and without the use of BMP.…”
mentioning
confidence: 99%
“…2 McAnany et al 2 conducted a meta-analysis of fusion rates after a known pseudarthrosis (not primary surgery), and fusion rates were higher after posterior surgery (97.1%) compared with anterior surgery (86.4%) in studies with a minimum follow-up of at least 6 months. In a large study from a multicenter health system, Guppy et al 31 evaluated 1158 patients undergoing all levels (1-5) of posterior cervical fusion, and the overall nonunion rate was ∼ 1.0%, with similar rates between non-BMP (0.7%) and BMP (1.1%) groups at a median follow-up of 1.7 years. Another retrospective series of 57 patients undergoing posterior cervical fusion by Dorward et al 32 reported a pseudarthrosis rate of 10.5%, though only 2 of 6 patients required revision surgery with a minimum of 2-year follow-up.…”
Section: Posterior Proceduresmentioning
confidence: 99%